Analisa Kepuasan Dan Kompensasi Terhadap Motivasi Serta Kinerja - Masiyah Masiyah; M. Naim Musyafik (Universitas Islam Kadiri, 2020)
With a significance level of 5%, the conclusions obtained conclusions: 1) Satisfaction has a positive and significant effect on motivation; 2) Compensation has a positive and significant effect on motivation; 3) Job satisfaction has a positive and significant effect on performance; 4) Compensation has a positive and significant effect on performance; 5) Motivation has a positive and significant effect on employee performance; 6) Job satisfaction has a positive and significant effect on performance through motivation; 7), Compensation has a positive and significant effect on employee performance through work motivation